A területfejlesztés finanszírozási rendszere az EU csatlakozás tükrében - Ruttkay, Éva (Tér és Társadalom, 1998)
National financial system of regional development finance system should be modernised and adjusted to the European standards. The approaching enlargement of the European Union raised the following issues: Adaptation of economic policy that should be focused on the improvement of competitiveness of the economy and ease of territorial differentiation; Enhancement of absorptive capacities including human, institutional and economic (financial) factors to obtain resources from EU funds; A new, decentralised model of financial framework should be established; A mid-term planning system must be formulated, including the elaboration of a national programming system that is adjusted to the EU standards and fitted into the national economic policy. To realise strategic purposes outlined above, institutions of territorial administration must be made operational furthermore, functions of central governmental and regional authorities should be clarified. The main constraint of the introduction of a new programming system is the recent financial policy that provide insufficient resources to ease regional differences and realise long-term development strategies. To set up a working programming system, financial conditions and institutional background must be improved furthermore, the programming process must be co-ordinated and an information and monitoring system should be established.